Use of Games as a Software Reuse Teaching Strategy - Castro, Diego Cardoso Borda; Werner, Claudia Maria Lima (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2025.10093, 2025)
Introduction: Software Reuse (SR) is a field rich in theoretical concepts that necessitates practical experience for optimal understanding. Nonetheless, the traditional approach to teaching SR is passive, lacking techniques that engage students or include practical elements in the subject. The use of games has been recommended as a solution for this issue and is already utilized in various Software Engineering disciplines; nevertheless, no games have been identified to teach SR. Objective: Therefore, this work aims to demonstrate the use of games for teaching SR. Methodology or Steps: The game created aims to teach software components, being one of the most used areas of SR in the job market, and was evaluated by 26 participants. Results: The evaluation demonstrated its pedagogical potential, showing that SR can be taught through games.